The Influence of Academic Culture and Knowledge Sharing on Green Innovation Performance - Kartika, Ika; Susita, Dewi; Yohana, Corry (IJHCM (International Journal of Human Capital Management), 2024)
This study investigates the influence of academic culture and knowledge sharing on green innovation performance at Mercu Buana University, Jakarta. A quantitative approach with a survey technique was employed to test the proposed hypotheses. The respondents comprised 100 lecturers selected through random sampling. Data were collected using questionnaires on academic culture, knowledge sharing, and green innovation performance, which were validated using the product moment correlation and reliability tested with Cronbach’s Alpha. Structural Equation Modeling with SmartPLS was applied for hypothesis testing and model evaluation. The findings reveal three key results. First, academic culture has a direct, positive, and significant influence on green innovation performance. Second, knowledge sharing positively and significantly affects green innovation performance. Third, academic culture exerts a direct and significant influence on knowledge sharing. Among the indicators, cooperation in academic tasks emerged as the strongest reflection of academic culture, while discussions between two or more parties proved to be the most influential indicator of knowledge sharing. Comfortable environmental innovation was found to be the most dominant indicator of green innovation performance. The study concludes that strengthening academic culture and promoting knowledge sharing are effective strategies to enhance green innovation performance in higher education institutions. These results provide theoretical implications for organizational behavior models and practical insights for universities to improve academic quality through sustainable innovation initiatives.